2013
DOI: 10.1021/jo401521y
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the Pyridine Directing Group from α-Substituted N-(Pyridin-2-yl)piperidines Obtained via Directed Ru-Catalyzed sp3 C–H Functionalization

Abstract: Two strategies, "hydrogenation-hydride reduction" and "quaternization-hydride reduction", are reported that make use of mild reaction conditions (room temperature) to efficiently remove the N-pyridin-2-yl directing group from a diverse set of C-2-substituted piperidines that were synthesized through directed Ru-catalyzed sp(3) C-H functionalization. The deprotected products are obtained in moderate to good overall yields irrespective of the strategy followed, indicating that both methods are generally equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 86 publications
(38 reference statements)
3
58
0
Order By: Relevance
“…The structure of 7a was unambiguously confirmed by single‐crystal X‐ray analysis (see the Supporting Information). Finally, the 2‐pyridyl directing group was removed from 3a by a two‐step procedure of quaternization and hydride reduction at room temperature to give parent oxindole 8 in 72 % isolated yield (Scheme c) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of 7a was unambiguously confirmed by single‐crystal X‐ray analysis (see the Supporting Information). Finally, the 2‐pyridyl directing group was removed from 3a by a two‐step procedure of quaternization and hydride reduction at room temperature to give parent oxindole 8 in 72 % isolated yield (Scheme c) …”
Section: Resultsmentioning
confidence: 99%
“…Removal of the Directing Group: Compound 3a (0.4 mmol) was dissolved in dry CH 2 Cl 2 (5 mL) in a round‐bottomed flask (25 mL) filled with nitrogen. The reaction mixture was cooled to 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Combined with our previous finding that the H/D scrambling of deuterated benzoxazole [D 1 ]2 a occurred much faster under similar reaction conditions, [8a-d,g] this result suggests that the C À H cleavage process of both the pyridone and the azole is facile and reversible in the present copperbased system. To our delight, the deprotection occurred readily at room temperature by quaternarization-driven [19] alcoholysis to furnish the corresponding heteroarylated 2-pyridone 3 ad' with a free NÀH group in acceptable yield (Scheme 7). On the basis of the above results and previously reported studies, we are tempted to assume a reaction mechanism as shown in Scheme 6.…”
Section: Methodsmentioning
confidence: 99%
“…4i, 14 The corresponding 6phenylthio-2-pyridone 6a was easily obtained from product 3a through a mild, two-step sequence in 66% yield (Scheme 2). Treatment of product 3a with 3-chloroperoxybenzoic acid (m-CPBA) at room temperature gave the corresponding sulfone 5a in 75% yield.…”
Section: Entrymentioning
confidence: 99%
“…of diphenyl disulde (2a) and 1.0 equiv. Other organic acids were less efficient (entries [14][15][16]. The structure of thiolated product 3a was conrmed by single-crystal X-ray analysis (Fig.…”
mentioning
confidence: 99%